2012
DOI: 10.1111/j.1743-6109.2012.02813.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflatable Penile Prosthesis and Salvage Protocol for Mechanical Failure: Is it Really Necessary?

Abstract: Introduction Penile prosthesis patients with mechanical failure who wish continued treatment require device removal and replacement. Infection rates as high as 18% have been reported for procedures involving replacement of malfunctioning penile prosthesis compared with 2% for primary implantation. Aim The aim of this study is to compare the outcomes of patients who have had a penile prosthesis replacement for mechanical failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Although the immediate salvage procedure has not been definitively compared with the delayed approach, its major hypothesized advantage is a lower risk of penile shortening on subsequent reimplantation of a new penile prosthesis with a potential to increase patient satisfaction [7,15,16]. Furthermore, recent studies have studied salvage, or revision, procedures in the context of mechanical prosthesis failure [6,[17][18][19]. Thus, it is relevant to study the Figure 1 displays the change in the national frequency of explantation vs. salvage over 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although the immediate salvage procedure has not been definitively compared with the delayed approach, its major hypothesized advantage is a lower risk of penile shortening on subsequent reimplantation of a new penile prosthesis with a potential to increase patient satisfaction [7,15,16]. Furthermore, recent studies have studied salvage, or revision, procedures in the context of mechanical prosthesis failure [6,[17][18][19]. Thus, it is relevant to study the Figure 1 displays the change in the national frequency of explantation vs. salvage over 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that a mini-salvage washout procedure may not be indicated for patients undergoing IPP replacement for mechanical failure. 59…”
Section: Resultsmentioning
confidence: 99%